(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses the relevance of music education and upbringing in preschool educational institutions. For preschool children, music education plays a crucial role not only in aesthetic development but also in the formation of social and emotional skills. The article analyzes how music education and upbringing impact children’s cognitive, emotional, and social development. It also highlights the importance of adapting music lessons to children’s psychology, the pedagogical methods and tools used, the significance of working with musical instruments, and key aspects of developing children’s musical abilities. The article emphasizes the necessity of effectively organizing and modernizing music education in preschool institutions.